Evaluation of Wound Healing Effect of Spirulina platensis Bioactive Molecules through a Multiligand In Silico Approach: Targeting TGF-β, TNF-α, VEGFR2, and KEAP1 - Muftiasih, Agnia; Munawaroh, Heli Siti Halimatul; Aisyah, Siti (Jurnal Kartika Kimia, 2025)
This study evaluates the therapeutic potential of bioactive molecules derived from Spirulina platensis such as gallic acid, quercetin, acacetin, and pinocembrin in promoting chronic wound healing using a multiligand in silico approach. This strategy may accelerate drug delivery by efficiently identifying potent candidates. Here, four key protein targets involve in wound healing, transforming growth factor-β (TGF-β), tumor necrosis factor-α (TNF-α), vascular endothelial growth factor receptor 2 (VEGFR2), and Kelch-like ECH-associated protein 1 (KEAP1), were selected based on their pivotal roles in modulating inflammatory responses, tissue proliferation, angiogenesis, and oxidative stress regulation. Molecular docking simulations revealed that the compound combinations of gallic acid–quercetin and acacetin–pinocembrin exhibited the most favorable binding affinities (−13.21 to −15.567 kcal/mol), surpassing the binding energies of native ligands. These combinations demonstrated strong potential to attenuate the overexpression of pro-inflammatory mediators (TGF-β and TNF-α) and to activate the Nrf2 antioxidant pathway through KEAP1 inhibition. Additionally, quercetin and pinocembrin were predicted to modulate VEGFR2-mediated angiogenesis in a controlled manner. Overall, Spirulina-derived bioactive displayed promising synergistic and multitarget interactions that could facilitate and accelerate the wound healing process. These findings provide a rational basis for the development of Spirulina-based topical therapeutics, although subsequent in vitro and in vivo validation is required to substantiate their efficacy